A comprehensive phylogenetic analysis of copper transporting P1B ATPases from bacteria of the Rhizobiales order uncovers multiplicity, diversity and novel taxonomic subtypes. Issue 4 (20th February 2017) - Cubillas, Ciro; Miranda‐Sánchez, Fabiola; González‐Sánchez, Antonio; Elizalde, José Pedro; Vinuesa, Pablo; Brom, Susana; García‐de los Santos, Alejandro
Abstract: The ubiquitous cytoplasmic membrane copper transporting P1B‐1 and P1B‐3 ‐type ATPases pump out Cu + and Cu 2+, respectively, to prevent cytoplasmic accumulation and avoid toxicity. The presence of five copies of Cu‐ATPases in the symbiotic nitrogen‐fixing bacteria Sinorhizobium meliloti is remarkable; it is the largest number of Cu + ‐transporters in a bacterial genome reported to date. Since the prevalence of multiple Cu‐ATPases in members of the Rhizobiales order is unknown, we performed an in silico analysis to understand the occurrence, diversity and evolution of Cu + ‐ATPases in members of the Rhizobiales order. Multiple copies of Cu‐ATPase coding genes (2–8) were detected in 45 of the 53 analyzed genomes. The diversity inferred from a maximum‐likelihood (ML) phylogenetic analysis classified Cu‐ATPases into four monophyletic groups. Each group contained additional subtypes, based on the presence of conserved motifs. This novel phylogeny redefines the current classification, where they are divided into two subtypes (P1B‐1 and P1B‐3 ). Horizontal gene transfer (HGT) as well as the evolutionary dynamic of plasmid‐borne genes may have played an important role in the functional diversification of Cu‐ATPases. Homologous cytoplasmic and periplasmic Cu + ‐chaperones, CopZ, and CusF, that integrate a CopZ‐CopA‐CusF tripartite efflux system in gamma‐proteobacteria and archeae, were found in 19 of the 53 surveyed genomes of the Rhizobiales . This result strongly suggests a high divergence of CopZ and CusF homologs, or the existence of unexplored proteins involved in cellular copper transport. Abstract : The presence of multiple copies of copper transporting P1B ‐type ATPases encoding‐genes with different evolutionary histories is a highly conserved characteristic in rhizobial genomes.We propose a novel four‐group and four‐subtype classification of Cu‐ATPases that redefines the current classification in two groups.